Insecticidal effects of deltamethrin in laboratory and field populations of Culicoides species: how effective are host-contact reduction methods in India?. Issue 1 (December 2017) - De Keyser, Rien; Cassidy, Clare; Laban, Swathi; Gopal, Prakash; Pickett, John; Reddy, Yarabolu; Prasad, Minakshi; Prasad, Gaya; Chirukandoth, Sreekumar; Senthilven, Kandasamy; Carpenter, Simon; Logan, James
Abstract Background Bluetongue virus (BTV) is transmitted byCulicoides biting midges and causes bluetongue (BT), a clinical disease observed primarily in sheep. BT has a detrimental effect on subsistence farmers in India, where hyperendemic outbreaks impact on smallholdings in the southern states of the country. In this study, we establish a reliable method for testing the toxic effects of deltamethrin onCulicoides and then compare deltamethrin with traditional control methods used by farmers in India. Results Effects of deltamethrin were initially tested using a colonised strain ofCulicoides nubeculosus Meigen and a modified World Health Organisation exposure assay. This method was then applied to field populations ofCulicoides spp. in India. The field population ofC. oxystoma in India had a greater LC50 (0.012 ± 0.009%) for deltamethrin than laboratory-rearedC.nubeculosus (0.0013 ± 0.0002%). Exposure ofC. nubeculosus to deltamethrin at higher ambient temperatures resulted in greater rates of knockdown but a lower mortality rate at 24 h post-exposure. Behavioural assays withC. nubeculosus in WHO tubes provided evidence for contact irritancy and spatial repellence caused by deltamethrin. The field experiments in India, however, provided no evidence for repellent or toxic effects of deltamethrin. Traditional methods such as the application of neem oil and burning of neem leaves also provided no protection. Conclusions Our study demonstrates that field-collectedCulicoides in India are less susceptible to deltamethrin exposure than laboratory-bredC. nubeculosus and traditional methods of insect control do not provide protection to sheep. These low levels of susceptibility to deltamethrin have not been recorded before in field populations ofCulicoides and suggest resistance to synthetic pyrethrioids. Alternative insect control methods, in addition to vaccination, may be needed to protect Indian livestock from BTV transmission.